2007
DOI: 10.1111/j.1365-2915.2007.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA detection rates of host mtDNA in bloodmeals of human body lice (Pediculus humanus L., 1758)

Abstract: Using polymerase chain reaction, we investigated the extent to which digestion affects the potential to amplify 12S mitochondrial DNA sequences from bloodmeals of individual human body lice (Pediculus humanus L.) (Phthiraptera, Pediculidae) up to 72 h after feeding on a surrogate rabbit host (Oryctolagus cuniculus L.) (Lagomorpha, Leporidae). Two rabbit-specific primer pairs were developed to produce amplicons of 199 bp and 283 bp, the smaller of which was found to have a significantly slower decay rate. Media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…We did not calculate decay rates for human DNA in bed bugs, because we found that recovery for any one time point was variable and a function of the blood meal or the individual bed bug. However, we did recover amplifiable human DNA up to 72 h after blood feeding with all 9 samples, as shown previously for rabbit DNA from body lice (Davey et al 2007).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…We did not calculate decay rates for human DNA in bed bugs, because we found that recovery for any one time point was variable and a function of the blood meal or the individual bed bug. However, we did recover amplifiable human DNA up to 72 h after blood feeding with all 9 samples, as shown previously for rabbit DNA from body lice (Davey et al 2007).…”
Section: Resultssupporting
confidence: 71%
“…Szalanski et al (2006b) identified a mtDNA marker 7 d post-blood feeding and a 271 bp STR marker 60 d post-blood feeding. When attempting to detect rabbit DNA in human body lice, Pediculus humanus humanus L. (Phthiraptera: Pediculidae), a 199 basepair (bp) amplicon had a significantly slower decay rate than a 283 bp amplicon, suggesting that amplicon size may be inversely proportional to decay rate (Davey et al 2007). We did not calculate decay rates for human DNA in bed bugs, because we found that recovery for any one time point was variable and a function of the blood meal or the individual bed bug.…”
Section: Resultsmentioning
confidence: 98%
“…Others have shown that mosquito midgut bacterial communities are dynamic and vary significantly with respect to bloodfed state (Wang et al., 2011). Host DNA is detectable by sequencing even when engorgement is no longer visible (Davey, Casey, Burgess, & Cable, 2007; Lee et al., 2002), and quite interestingly, we identified 18S rRNA sequences belonging to phylum Chordata, class Mammalia, in a few of our mosquito samples. Although their presence was not frequent enough across pools to conduct further analyses, with the everimproving depth of sequencing provided by technological advances, we envision future studies being able to simultaneously characterize both microbial community composition and vertebrate host utilization from field‐collected mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial DNA is a commonly used and effective target for bloodmeal assays because of its high copy number and rapid rate of evolution relative to nuclear DNA (Kent 2009). Optimal amplicon size for real-time assays using SYBR Green I as a ßuorescent reporter is between 75 and 200 base pairs (bp) (Bio-Rad Laboratories 2006), and the ability to detect partially digested bloodmeals via PCR appears to be inversely related to amplicon size (Kirstein and Gray 1996, Kent and Norris 2005, Davey et al 2007). Therefore, we sought to identify primers that would amplify a relatively small mitochondrial gene fragment from vertebrates without amplifying ßea DNA.…”
Section: Methodsmentioning
confidence: 99%